2007
DOI: 10.1016/j.rapm.2007.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Effects of Thoracic Epidural Analgesia in Ovine Hyperdynamic Endotoxemia

Abstract: Background and Objectives:Thoracic epidural analgesia (TEA) is increasingly used for perioperative analgesia. If patients with TEA develop sepsis or systemic inflammatory response subsequent to extended surgery the question arises if it would be safe to continue TEA with its beneficial effects of improving gastrointestinal perfusion and augmenting tissue oxygenation. A major concern in this regard is hemodynamic instability that might ensue from TEA-induced vasodilation. The objective of the present study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Although the use of TEA exhibited hemodynamic stability in hyperdynamic and hypodynamic sepsis, we are unable to comment on TEA-related actions on other organ systems. In this regard, however, it is noteworthy that the use of TEA in both hypodynamic and hyperdynamic endotoxemic sheep did not impair hemodynamics beyond the changes caused by endotoxin itself [32,33]. Although the use of TEA in critically ill patients has gained increasing interest in the recent years, its use in the intensive-care setting remains controversial [2-4].…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of TEA exhibited hemodynamic stability in hyperdynamic and hypodynamic sepsis, we are unable to comment on TEA-related actions on other organ systems. In this regard, however, it is noteworthy that the use of TEA in both hypodynamic and hyperdynamic endotoxemic sheep did not impair hemodynamics beyond the changes caused by endotoxin itself [32,33]. Although the use of TEA in critically ill patients has gained increasing interest in the recent years, its use in the intensive-care setting remains controversial [2-4].…”
Section: Discussionmentioning
confidence: 99%
“…[16] Studies on endotoxemic animal models have also shown that there is no impairment of hemodynamics following segmental TEB with 0.1% bupivacaine beyond the changes caused by sepsis per se . [1718] Of course, maintenance of blood pressure after the epidural block using fluids and vasopressor boluses must continue to be a clinical goal as in the routine application of the technique. Regarding the apprehension of infective neurological complications when employing the block in septic patients, its rarity (<1%) requires a very large sized clinical trial to address the issue conclusively.…”
mentioning
confidence: 99%